Westonci.ca is the ultimate Q&A platform, offering detailed and reliable answers from a knowledgeable community. Explore thousands of questions and answers from a knowledgeable community of experts ready to help you find solutions. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
Answer:
B) 2+4x=5-3x-3
Step-by-step explanation:
Terms and topics
- Linear equations with one unknown.
Why learn this
- Linear equations cannot tell you the future, but they can give you a good idea of what to expect so you can plan ahead. How long will it take you to fill your swimming pool? How much money will you earn during summer break? What are the quantities you need for your favorite recipe to make enough for all your friends?
- Linear equations explain some of the relationships between what we know and what we want to know and can help us solve a wide range of problems we might encounter in our everyday lives.
PROBLEM:
[tex]2+4x=5-\left(3\cdot\left(x+1\right)\right)[/tex]
STEP 1:
Solve by distributing:
[tex]2+4x=5-\left(3x+3\cdot1\right)[/tex]
Simplify the arithmetic:
[tex]2+4x=5-\left(3x+3\right)[/tex]
Expand the parentheses:
[tex]2+4x=5-3x-3[/tex]
Group like terms:
[tex]2+4x=-3x+\left(5-3\right)[/tex]
Simplify the arithmetic:
[tex]2+4x=-3x+2[/tex]
STEP 2:
Group all x terms on the left side of the equation
[tex]2+4x=-3x+2[/tex]
Add 3x to both sides:
[tex]2+4x+3x=-3~x+2+3x[/tex]
Group like terms:
[tex]4x+3x+2=-3x+2+3x[/tex]
Simplify the arithmetic:
[tex]7x+2=-3x+2+3x[/tex]
Group like terms:
[tex]7x+2=-3x+3x+2[/tex]
Simplify the arithmetic:
[tex]7x+2=2[/tex]
Step 3:
Group all constants on the right side of the equation
[tex]7x+2=2[/tex]
Subtract 2 from both sides:
[tex]7x+2-2=2-2[/tex]
Simplify the arithmetic:
[tex]7x=2-2[/tex]
Simplify the arithmetic:
[tex]7x=0[/tex]
Isolate the X:
[tex]x=0[/tex]
Now we have to find the equivalent equation,
(NO STEPS - MAXES OUT BRAINLYS CHARACTERS)
A) 2 + 4x = 2x - 3 = [tex]x=\frac{-5}{2}[/tex]
B) 2+4x=5-3x-3 = x = 0 ( since it's the correct answer, I have to prove how).
1. Simplify the expression
2+4x=5-3x-3
Group like terms:
[tex]2+4x=-3x+\left(5-3\right)[/tex]
Simplify the arithmetic:
[tex]2+4x=-3x+2[/tex]
2. Group all k terms on the left side of the equation
[tex]2+4x=-3x+2[/tex]
Add 3x to both sides:
[tex]2+4x+3x=-3~x+2+3x[/tex]
Group like terms:
[tex]4x+3x+2=-3x+2+3x[/tex]
Simplify the arithmetic:
[tex]7x+2=-3x+2+3x[/tex]
Group like terms:
[tex]7x+2=-3x+3x+2[/tex]
Simplify the arithmetic:
[tex]7x+2=2[/tex]
3. Group all constants on the right side of the equation
[tex]7x+2=2[/tex]
Subtract 2 from both sides:
[tex]7x+2-2=2-2[/tex]
Simplify the arithmetic:
[tex]7x=2-2[/tex]
Simplify the arithmetic:
[tex]7x=0[/tex]
Isolate the X:
[tex]x=0[/tex]
Now that we have analyzed and figured out each problems, using the process of elimination strategy to find our answer, we have finalized the correct answer.
So therefore, your answer is B.
We appreciate your time. Please come back anytime for the latest information and answers to your questions. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.